2015
DOI: 10.1021/ja512112j
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Protein Crystallography of Biaryltriazoles as Potent Tautomerase Inhibitors of Macrophage Migration Inhibitory Factor

Abstract: Optimization is reported for biaryltriazoles as inhibitors of the tautomerase activity of human macrophage migration inhibitory factor (MIF), a proinflammatory cytokine associated with numerous inflammatory diseases and cancer. A combined approach was taken featuring organic synthesis, enzymatic assaying, crystallography, and modeling including free-energy perturbation (FEP) calculations. X-ray crystal structures for 3a and 3b bound to MIF are reported and provided a basis for the modeling efforts. The accommo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
135
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(140 citation statements)
references
References 35 publications
(97 reference statements)
5
135
0
Order By: Relevance
“…Furthermore, a very potent inhibitor for the macrophage migration inhibitory factor (MIF or MMIF) was developed with the help of FEP calculations. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a very potent inhibitor for the macrophage migration inhibitory factor (MIF or MMIF) was developed with the help of FEP calculations. 23 …”
Section: Introductionmentioning
confidence: 99%
“…These residues establish interactions with the inhibitor in the crystal structure of the Hu‐MIF/inhibitor complex (PDB entry: 4WR8). In that complex, the polar residues Lys32 and Ser63 bind biaryltriazoles by hydrogen bonds, while Pro33, Tyr36, Trp108, and Phe113 keep the inhibitor bound by stacking interactions . Our structural alignments showed that all of these relevant residues (ie, Lys32, Pro33, Tyr36, Ser63, Trp108, and Phe113) were 100% conserved in Ts‐MIF with a very similar spatial orientation compared with Hu‐MIF (Figure 2B).…”
Section: Resultsmentioning
confidence: 90%
“…26 First, a single point screening was done at a concentration of 25 μM and 50 μM and the compounds showing more than 50% inhibition of enzyme activity at 25 μM were tested for IC 50 values (Figs. S2 and S3).…”
Section: Resultsmentioning
confidence: 99%
“…The assay was done following the procedure of Dziedzic et al 26 4-hydrox-yphenyl pyruvate (4-HPP) was used as substrate to quantify tautomerase activity. Stock solutions of 10 mM 4-HPP were made in 50 mM ammonium acetate buffer pH 6.0, and incubated overnight at room temperature to allow equilibration between keto and enol form.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation